Modelling the determinants of behavioural likelihood to engage in community-based surveillance of infectious diseases among community representatives in Kelantan, Malaysia - Hasan, Ahmed Azeez (2025)
Community-based surveillance (CBS) is relatively new strategy for early detection of infectious disease. It involves community members actively participate in detecting and reporting changes in health patterns within their communities to health authorities, facilitating disease containment before outbreaks become widespread and difficult to control. However, community participation in CBS remains limited, and factors influencing engagement, such as knowledge, attitudes, and perceptions, are understudied. Additionally, no validated measurement tool exists to assess these factors. This study aimed to develop and validate a Malay language Knowledge, Attitudes, and Perception’s questionnaire, grounded in the Theory of Reasoned Action and the Health Belief Model, to identify determinants of community participation in CBS. The study was conducted in three phases using a cross-sectional design. In Phase I, a questionnaire (KAP-CBS-ID) was developed and translated to Malay. It comprised three main sections—knowledge, attitude, and perception—each with three domains. The knowledge section covered knowledge about infectious diseases, CBS, and community-level case definition; the attitude section initially addressed subjective norms, intention to participate, and behavioural likelihood; and the perception section included perceived susceptibility, perceived benefits, and self-efficacy. Content validation was performed by public health and epidemiology experts, and face validation and pretesting were conducted with community representatives. In Phase II, the questionnaire was tested with 152 participants using 2-parameter logistic Item Response Theory (2-PL IRT) for knowledge section, and Exploratory Factor Analysis (EFA) for attitude and perceptions. The 2-PL IRT of for knowledge retained 31 of 45 items after removing poorly performing ones. The EFA confirmed a multidimensional structure for attitudes and perceptions, revealing additional factors: negative attitudes and perceived barriers under attitude and perception respectively. Reliability analysis showed good internal consistency (Cronbach’s alpha: 0.71–0.91), with the attitude and perception sections explaining 50.8% and 58.7% of the variance, respectively. Phase III involved Confirmatory Factor Analysis (CFA) and Structural Equation Modelling (SEM) with 470 participants. CFA supported the measurement models with satisfactory fit indices. The SEM, integrating components of TRA and HBM. SEM analysis revealed significant positive associations between knowledge of infectious diseases, subjective norms, and intention to participate, while negative attitudes had an inverse relationship. Behavioural likelihood was positively influenced by intention, perceived susceptibility, and benefits but negatively affected by perceived barriers. Self-efficacy strongly influenced perceived benefits and susceptibility. The model explained 46.1% of behavioural likelihood variance, 57.0% of intention, 70.4% of perceived susceptibility, and 61.7% of perceived benefits. In conclusion, the study successfully developed and validated the Malay KAP-CBS-ID questionnaire, demonstrating good reliability and validity. Key findings highlighted the importance of addressing knowledge gaps, fostering positive attitudes, and reducing barriers to enhance community participation in CBS. This tool provides a foundation for future research and interventions to strengthen CBS systems, improving early disease detection and outbreak control